Left Imaginal Neglect in Heminattention: Experimental Study with the O’Clock Test - D. Grossi; R. Angelini; A. Pecchinenda; L. Pizzamiglio (Behavioural Neurology)
Both sensory and imaginal defects have been reported in unilateral neglect, but their assessment based on the description of famous squares can be difficult in a clinical setting. The O'clock Test is an alternative tool for revealing imaginal defects. Our aim was to demonstrate imaginal neglect in patients with left heminattention. Ten patients were studied and a mild unilateral defect in imaginal processes was found with an increase in the defect when the patients were fatigued.